Disseminated cutaneous leishmaniasis: lesional polymorphism and late diagnosis in an immunocompetent patient - Dadalto Fiorott, Barbara; Falqueto, Aloísio; Tristão Sá, Ricardo; Amaral de Moura, Luana (Revista de Patologia Tropical / Journal of Tropical Pathology, 2023)
Tegumentary leishmaniasis (TL) is considered a neglected tropical disease and it is endemic in Brazil. Among the wide morphological spectrum that composes TL, the disseminated cutaneous leishmaniasis (DL) stands out, which is characterized by multiple lesions in two or more non-contiguous body regions. This clinical form may be rarely associated with immunosuppression. The wide range of cutaneous manifestations is a remarkable DL feature, and its diagnosis may represent a challenge even for the specialists and experienced professionals. We report a case of an immunocompetent 55-year-old man, who has presented with polymorphic and disseminated skin lesions and he was treated incorrectly due to the absence of clinical suspicion of leishmaniasis. KEY WORDS: Leishmania; Leishmania braziliensis; leishmaniasis.